(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study analyzes the characteristics of Beta-lactam antibiotic utilization at Thu Duc City Hospital (TDCH) from January to June 2024. Methods: A cross-sectional descriptive study was conducted through data collection on Beta-lactam antibiotic utilization in treating patients covered by health insurance at TDCH during the specified period. Utilization characteristics were analyzed based on antibiotic subgroups, country of manufacture, administration routes, drug composition, treatment scope. The analysis was performed through total drug quantity, total expenditure, and corresponding percentage distribution. Results: During the study period, 78 Beta-lactam antibiotics were used, with outpatient antibiotic expenditures accounting for 52.3% of total costs. The Penicillin subgroup included 35 drugs (45%), representing 68.2% of total antibiotic expenditures. Amoxicillin + Clavulanic acid was the most frequently used and highest-cost antibiotic among the 23 active ingredients in the study sample. Domestically produced Beta-lactam antibiotics accounted for 78.8% of total costs, while combination antibiotics represented 73.2% of expenditures. Carbapenems were administered exclusively via injection, with 79.8% of their costs associated with single-agent antibiotics and 99.5% of their costs linked to inpatient treatment. Conclusion: This study provides detailed insights into Beta-lactam antibiotic utilization at TDCH, serving as a basis for hospital management to adjust and optimize strategies for managing this drug group.